DAMPAK GAME ONLINE TERHADAP HASIL BELAJAR SISWA (KAJIAN LITERATUR) - Pantas, Hendrik (Jurnal Curere, 2025)
Eespecially those related to smart computer technology, are growing rapidly. Until the first cell phones were used to fulfill communication needs, now cellphones can be used to do many things, such as being used to search for any information in the world very easily, playing online games anywhere and so on. Mobile Legend games are very popular. Not only by teenage boys, now there are many girls who like to play these online games. The Mobile Legends application: Bang Bang has been downloaded more than 100 million times. By playing online games such as Mobile Legends, it can affect student learning outcomes. Learning is an activity that is important for everyone. Therefore, if a child's learning is disrupted because of online games, it will affect student learning outcomes. Learning outcomes are a change in behavior that occurs in a person that can be observed. With these learning outcomes, we can improve our abilities and talents.